2019
DOI: 10.3390/app9194087
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations on the Temperature Increase of Ultra-High Performance Concrete under Fatigue Loading

Abstract: Leaner, more filigree, and resource-saving constructions are the development goal of the in the building industry. In reinforced concrete construction, a ultra-high strength concrete was developed to achieve these goals. Due to its use and requirements, this very pressure-resistant material is no longer only exposed to static loads. In applications such as wide-span bridges, machine foundations and wind turbines, the susceptibility to vibration is also significant. Research into the fatigue behavior of the new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(57 citation statements)
references
References 7 publications
2
35
0
2
Order By: Relevance
“…Another hypothesis from Teichen 16 indicates that a major part of the dissipated energy E δ is transformed into thermal energy. This hypothesis was already confirmed in a previous paper 17 and is in accordance with the observed warming of concrete specimens during fatigue tests 2–10 . Also, the explanation from Whaley 18 and Chen et al, 19 that the friction and sliding processes between cracks and around the grains are responsible for the hysteresis and therefore for the dissipation energy E δ , supports this hypothesis.…”
Section: Dissipation Energysupporting
confidence: 83%
See 1 more Smart Citation
“…Another hypothesis from Teichen 16 indicates that a major part of the dissipated energy E δ is transformed into thermal energy. This hypothesis was already confirmed in a previous paper 17 and is in accordance with the observed warming of concrete specimens during fatigue tests 2–10 . Also, the explanation from Whaley 18 and Chen et al, 19 that the friction and sliding processes between cracks and around the grains are responsible for the hysteresis and therefore for the dissipation energy E δ , supports this hypothesis.…”
Section: Dissipation Energysupporting
confidence: 83%
“…Besides the analysis of the strain development and the degradation of stiffness during fatigue tests, the warming of the specimens was being on focused more in the past 2–10 . It was shown that specimens were heated up dependent on the stress amplitude, the maximum stress level and the loading frequency.…”
Section: Introductionmentioning
confidence: 99%
“…B. im Verbundforschungsvorhaben „WinConFat“ zeigen, dass es bei Ermüdungsversuchen mit üblichen Belastungsfrequenzen zwischen 1 Hz ≤ f P ≤ 10 Hz insbesondere auf Oberspannungsniveaus 0,75 ≥ S max ≥ 0,60 ( S min = 0,05) zu deutlichen Temperaturerhöhungen der Probekörper kommt [25–27]. Die Temperaturerhöhungen sind von verschiedenen Faktoren abhängig und bei hochfesten Betonen besonders stark ausgeprägt [28–31]. Diese entstehen durch die im Probekörper umgewandelte Dissipationsenergie [32, 33].…”
Section: Anwendungsgrenzen Des Konzeptsunclassified
“…In order to be able to reproduce a significant number of load changes in a short time, the loading speed is usually set high. In the case of HPC and UHPC; however, this leads to heating of the specimen, sometimes to the point of failure 2–10 . Because the samples fail earlier than the calculated expected values according to fib Model Code 2010, 11 special attention must be paid to heating.…”
Section: Introductionmentioning
confidence: 99%
“…In the project “Influence of load‐induced temperature fields on the fatigue behaviour of UHPC subjected to high frequency compression loading,” a comprehensive parameter study was therefore being carried out to understand which parameters have an influence on temperature development. The concrete strength, 3 the maximum grain size, 9 as well as the frequency and the upper 2,3,9 and the lower stress 3 were varied. In Reference 9, the heating rate was introduced as a possibility for a detailed analysis of the temperature development.…”
Section: Introductionmentioning
confidence: 99%